Ameliorative Effects of Hesperidin on Piroxicam-Induced Haemato-Biochemical Alterations in Rats - Patel, Sneha A; Vihol, Priti D; Patel, Jignesh M; Varia, Rasesh D; Parmar, Hitesh C; Baraiya, Parth D; Panzade, Pranav R (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Piroxicam, a non-steroidal anti-inflammatory drug, is widely prescribed in various inflammatory disorders. However, it causes side effects like hepato-renal toxicity, foetotoxicity and gastrointestinal toxicity etc. presumably due to production of oxidative stress. The bioflavonoid hesperidin, a flavanone glycoside, is reported to have many health benificial effects. The present study was designed to investigate the possible protective effects of hesperidin against piroxicam induced toxicity in male Wistar rats. Forty rats were divided into five groups with eight rats in each group. Groups I, II, III, IV and V were administered orally daily for 28 days with 1% carboxy methyl cellulose (CMC), piroxicam @ 10 mg/kg. b. wt., piroxicam @ 25 mg/kg. b. wt., piroxicam @10 mg/kg. b. wt. along with hesperidin @ 160 mg/ kg. b. wt. and piroxicam @ 25 mg/kg. b. wt. along with hesperidin @ 160 mg/kg. b. wt., respectively. The results revealed that piroxicam @ 10 mg/kg b.wt. (Gr. II) caused no changes in haemato-biochemical parameters, while @ 25 mg/kg b. wt. (Gr. III) caused significant decrease in TEC, Hb, PCV, MCH, MCHC and platelet counts, and increase in TLC, neutophils and lymphocyte count in comparision to control Gr. I animals. Piroxicam caused significant increase in serum levels of liver and kidney function parameters including AST, total protein, BUN and creatinine as well as it also altered lipid metabolism @ 25 mg/kg b. wt.. The hesperidin was found to be effective against piroxicam induced pathological effects suggesting that hesperidin can be recommended to reduce the toxic effects produced by piroxicam.